The Generosity Education for Children through Quranic Verses for Islamic Philanthropy Awareness - Saiful Bahri; Adlan Fauzi Lubis; Muhammad Choirin; Andry Setiawan (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
The rapidly growing number of children is a demographic boon for Indonesia. There is positive potential with this number. However, there are also threats amidst the onslaught of several hedonic cultures and the unpredictable era of disruption. The potential for zakat in Indonesia is increasing, but the realization rate is still small. Therefore, effective early education is needed to encourage children's understanding of the importance of the character of generosity. The Quran emphasizes the obligation of zakat. In addition, these verses have a revelation from obligatory to sunnah. This research aims to examine the correlation of Quranic verses for Islamic philanthropy awareness, which include zakat, infaq, and sadaqah as a medium for instilling the character of generosity in children; 1) How is the leveling of Quranic verses about islamic philanthropy? 2) How do we recommend children for zakat, infaq and sadaqah? This research uses a descriptive qualitative method with a thematic approach. It is hoped that there will be a conceptual model for cultivating the character of generosity in children to prepare them to become contributive individuals who can build progress and welfare for the nation.